1998
DOI: 10.1093/ndt/13.5.1206
|View full text |Cite
|
Sign up to set email alerts
|

High dose enalapril impairs the response to erythropoietin treatment in haemodialysis patients

Abstract: High-dose enalapril increases rHuEpo requirement and should be reserved for dialysis patients with hypertension uncontrollable with other antihypertensive medications or dialysis patients with cardiac failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 1 publication
2
85
1
1
Order By: Relevance
“…19 In our study, baseline Hgb in patients receiving ACE inhibitors was no different from that in patients not receiving them. Although the exact reason for this discrepancy with the literature is unclear, patients not receiving ACE inhibitors in Val-HeFT had more severe HF.…”
Section: Should Anemia In Hf Be Treated?contrasting
confidence: 46%
See 1 more Smart Citation
“…19 In our study, baseline Hgb in patients receiving ACE inhibitors was no different from that in patients not receiving them. Although the exact reason for this discrepancy with the literature is unclear, patients not receiving ACE inhibitors in Val-HeFT had more severe HF.…”
Section: Should Anemia In Hf Be Treated?contrasting
confidence: 46%
“…18 Use of ACE inhibitors may reduce Hgb by inhibiting erythropoietin synthesis. 19 Iron deficiency resulting from malabsorption, nutritional deficiencies, impaired metabolism, 20 and aspirin-induced gastrointestinal bleeding may contribute. Finally, hemodilution caused by an increase in plasma volume has been found to cause anemia in nearly half the patients with severe end-stage HF.…”
Section: Causes Of Anemia In Hfmentioning
confidence: 99%
“…In addition, ACE inhibitors may impair erythropoiesis via either suppression of angiotensin-mediated Epo production or bone marrow response to Epo [53]. The relationship between the use of ACEI and ERI is still controversial, some investigations showed no relationship [54][55][56] while others [57,58] confirmed this study's finding and showed reduction in response to ESA. This study showed a positive significant association between statins use and ERI.…”
Section: Individual Response Variations To Erythropoietin Stimulatingsupporting
confidence: 69%
“…These studies have disagreed as to the role of ACE inhibitors on erythropoietin production and effectiveness (4). Some groups suggest that ACE inhibitors reduce erythropoietin levels or induce resistance to erythropoietin (6,22,23,26). Other studies find no causative link between erythropoietin and the anemia induced by ACE inhibitors or AT 1 receptor antagonists (3,24,27,28).…”
Section: Figurementioning
confidence: 99%